Pendidikan Karakter Berbasis Keagamaan (Studi Kasus di SDIT Nur Hidayah Surakarta) - Fauzi Annur (Fakultas Ilmu Tarbiyah dan Keguruan (FITK), Institut Agama Islam Negeri (IAIN) Surakarta, 2016)
Until now, the education system in our country is more emphasis on the cognitive aspect than educating for character. Meanwhile, the globalization in 21st has given rise to the phenomenon of free trade, dependence science and technology (ICT, Bio-technology, Nano-technology), global life (Speed, Conectivity, Intangable, and Compatibility), human rights, issues of democratization, environment, gender, and multiculturalism. SDIT Nur Hidayah is a school has applied to try appliying character building. These programs of character building is implementating from their own religion. This research uses descriptive qualitative. Subject of these researchs are teachers and students. And informan of these researchs are headmaster, employees, and parents of the children.The results of this research shows that the information program of the characters in SDIT Nur Hidayah Surakarta applied intensively (daily, weekly, monthly). The programs include 1. integrated in the leraning process, 2. any other programs: Pekan Pembiasaan, Pekan Kedisiplinan, Mentoring, Mutaba’ah Alyaumiyah. The purpose of these programs is intended to build characters of the students. These programs are not only comprehensive, but also very unique. The children are so enjoy and enthusiastic in carrying out various characters, and we hope they have a basic foundation of strong character.Keywords: Character Building, based on Religion